Antidiabetic activity test of infusion combination rosella flower (Hibiscus sabdariffa L.) and cinnamon bark (Cinnamomum burmannii (Nees & T. Nees) Blume) in male mice (Mus musculus) induced by alloxan - Chaerul, Rasid; Mercya, Yovita (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
Diabetes Mellitus (DM) is a disorder of carbohydrate, lipid and protein metabolism which is characterized by increased blood glucose levels. The existence of DM as a public health problem is increasing globally. This experimental research was carried out to determine the activity of a combination of rosella flower infusion and cinnamon bark on blood glucose levels in male mice that had been induced by alloxan. After ensuring that the blood glucose level of the mice was >175 mg/dl, 4 groups were tested, namely test group 1 was given a single rosella flower infusion, test group 2 was given a single cinnamon bark infusion, test group 3 was given a combination of rosella flower infusion and stem bark cinnamon, and the control group were given aqua destillata. Based on the results of the Kruskal-Wallis non-parametric statistical test, it shows a value of p = 0.009 (p £ 0,05), which means there is a difference in the reduction in blood glucose levels between the test groups. Then, to determine the greatest decrease in glucose levels, a Post Hoc test was carried out and the highest mean rank value was obtained (13.00) in the infusion group of the combination of rosella flowers and cinnamon bark, followed by the cinnamon bark infusion group (5.80), and the rosella flower infusion group (5.20).